Compounds from the XeF2–TaF5 System: Novel Synthesis and Crystal Structures - Uran, Erik (Bulletin of Chemists and Technologists of Bosnia and Herzegovina, 2022)
Xenon difluoride (XeF2) is a powerful oxidant and a medium-strong fluoride-ion donor. This is manifested in its reaction with Lewis-acidic pentafluorides of p-block and transition elements, such as AsF5, SbF5, BiF5, NbF5, TaF5, RuF5, IrF5, and AuF5, forming either [XeF]+ or [Xe2F3]+ species. Although the structural investigation of compounds with p-block pentafluorides has been carried out extensively, in the case of transition metals, only the crystal structures of the ruthenium(V) and iridium(V) analogues have been reported. Typically, these compounds are synthesized in anhydrous HF solutions or in XeF2 melts. In this work, a new convenient and readily available synthetic method was developed and optimized for the XeF2–TaF5 system. This has afforded a facile access to [XeF][TaF6], [XeF][Ta2F11], and [Xe2F3][TaF6] compounds, which were characterized by vibrational spectroscopy (Raman, ATR-FTIR) and X-ray diffraction techniques. Moreover, their crystal structures were determined for the first time by low-temperature single-crystal X-ray diffraction. The structures of [XeF]+[TaF6]− and [XeF]+[Ta2F11]− consist of tight ion pairs, whereas weakly interacting V-shaped cations [Xe2F3]+ and octahedral [TaF6]– anions are observed in the [Xe2F3][TaF6] salt.